The Kantian Progress of the Unsociables: Bridging History and Morals in an Agonistic Reality - Pinheiro, Inês (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The point of departure for this paper is the question: “Where does the Kantian progress leave the most vulnerable?” Consequently, our aim is to study the idea of “progress” in the practical realm of Kant’s thought, namely in its political, social, and historical dimensions, while relating it with the anthropological notion of “unsocial sociability”. By doing so, our ultimate goal is to propose a reflection on Kantian progress that questions how it copes with reality, not only in the broad sense of its possibility, but mainly when it comes to tackling the agonistic arena of our societies where we can’t escape the existence of social conflicts that leave many in suffering and vulnerability.